Orchid Care: an exploration in experiential and theoretical environmental care practice shown to orchids through the Anthropocene - Croukamp, Bradley (Department of Biological Sciences, 2025)
This thesis is an exploration in experiential and theoretical environmental care practice shown to orchids through the Anthropocene. It revolves around two African orchid species, one in Cape Town and one in Zimbabwe, and the care practices shown to these plants. The thesis explores the question: in what way does an orchid's status generate a level of institutional care that attempts to protect the plants? Chapter 1 explores the idea of orchid status through colonial collection. Chapter 2 focuses on the reactionary rules that came about after this exploitation. In addition, this chapter deals with the structure of CITES and what happens when orchids are over-collected because of their status. These ideas and themes of status and collection are applied to the case studies in Chapter 3, with special focus on field philosophy. Storytelling is used as the basis for Chapter 3, personal experience and primary research informs this chapter to interrogate care practices that surround the case studies . Major influences on the interactions throughout this thesis are theorists Anna Tsing, Thom Van Dooren, Donna Harraway and Amy Hinsley. These theorists deal with anthropogenic landscapes and ways of being that navigate the Anthropocene which is a lens used throughout this thesis in an attempt to answer the research question.